Conflicts for the memory and for the past - Pérez Cortés, Sergio (Estudios de Filosofía, 2008)
Memory poses the complex problem of the insertion of the subject in his community. It is neither purely individual because it allows the subject to be embedded in the symbolic order of culture and time, nor is it entirely social since shared memory must still be processed by the individual. Memory is both an experience of the subject with himself and an experience of the subject’s relationship with his Other. This explains why our starting point is to show what in memory allows the subject to get hooked on the symbolic order of culture, and then examine the field of current experience of collective memory. An attempt will therefore be made to briefly describe the passage from memory to memory, from memory to the past and from this to history, under a guiding idea: the past, which is indeterminate, is only available through individual and collective recollection, that is Sure; rather, the question to be examined will be the difficulties in making the memory. [Fragment]